단순악관절 잡음군에서 좌/우 진동 감별방법 연구 - 정다운(Da-Un Jung); 강동완(Dong-Wan Kang) (Journal of dental rehabilitation and applied science, 2016)
Purpose: study for discriminating method of origin side vibration from non-symptomatic clicking group. Materials and Methods: 60 joints vibrations of 30 subjects in non-symptomatic clicking group was recorded via subject's awareness, examiner's palpation and JVA analysis. Origin side vibration was discriminated with consideration for frequency spectrum, time delay and phase shift of waveforms, analysis of numeric values. Results: There were all unilateral vibrations with JVA analysis and number of origin vibrations were 42. 11 pairs of vibrations showed time delay and phase shift and transferred side vibrations showed smaller values of total integral and bigger values of > 300 / < 300 ratio than origin side vibrations except one pair of vibrations. Also as the ipsi-lateral joint vibrations with smaller values of total integral showed bigger values of > 300 / < 300 ratio than the contra-lateral joint vibrations and there all ipsi-lateral vibrations were showed small values of total integral below 10 and hard to detect time delay and phase shift. So the features were used in discrimination of origin side vibrations. Conclusion: There should be all-around considerations for discrimination of origin side vibrations that is frequency spectrum, phase shift and time delay and analysis of numeric values. 목적: 단순악관절 진동군에서 좌/우 진동 중 유의한 진동의 감별법을 연구하는 것이다. 연구 재료 및 방법: 단순악관절 진동만을 갖고 있고 측두하악관절 질환의 제 증상이 없는 단순악관절 진동그룹 30명의 60개 관절에서 44쌍의 진동을 기록하였고 대상자의 인지와 검사자의 촉진, JVA 검사 결과를 비교하였다. JVA로 기록된 진동의 주파수 스펙트럼, 진동파형 시간차 위상변위 분석, 수치 분석을 통해 좌/우 진동 중 유의한 진동을 감별하였다. 결과: JVA 분석결과 양측성 진동은 한 건도 없었으며 유의한 편측 진동은 42개로 감별되었다. 시간차 위상변위를 보이는 것은 11쌍이었고 이 중 한 쌍을 제외한 모든 진동에서 전달된 측의 진동이 발생측 진동보다 진동 총에너지(total integral) 값은 더 작고 > 300 / < 300 ratio는 같거나 더 큰 특징을 보이는 것을 관찰하였다. 또한 진동 총에너지 값이 10 이하로 작고 시간차 위상변위를 보이지 않아 좌/우 감별의 근거가 모호한 나머지 진동 모두에서 진동 총에너지 값이 더 작은 쪽의 > 300 / < 300 ratio가 더 큼을 관찰하여 이를 좌/우 감별의 근거로 삼을 수 있었다. 결론: JVA로 좌/우 진동 중 유의한 진동을 감별하기 위해서는 주파수 스펙트럼, 시간차 위상변위 및 수치 분석 등이 모두 고려되어야 한다.